The Effect of Phonological Abilities for Children in Communication - Yani Lubis; Nury Ana Harahap; Putri Nur Aisyah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research entitled "The Effect of phonological abilities for children in Communication".Â  The purpose of this study was to examine the impact of children's phonological skills on communication. The purpose of this study is to describe children's language acquisition in terms of phonology, including the acquisition of vowels and consonants, and the factors that influence phonological acquisition in communication.The study data are conversations between subjects and their mothers, grandmothers, and other family members and the community. Data collection techniques were performed using recording techniques, notes, and Google Forms. We then analyze the data obtained and use them to conclude stages of language acquisition at the phonological, syntactic, semantic and pragmatic levels.Â